Precise Modulation of the Breathing Behavior and Pore Surface in Zr‐MOFs by Reversible Post‐Synthetic Variable‐Spacer Installation to Fine‐Tune the Expansion Magnitude and Sorption Properties. Issue 34 (12th July 2016) - Chen, Cheng‐Xia; Wei, Zhangwen; Jiang, Ji‐Jun; Fan, Yan‐Zhong; Zheng, Shao‐Ping; Cao, Chen‐Chen; Li, Yu‐Hao; Fenske, Dieter; Su, Cheng‐Yong
Abstract: To combine flexibility and modifiability towards a more controllable complexity of MOFs, a post‐synthetic variable‐spacer installation (PVSI) strategy is used to implement kinetic installation/ uninstallation of secondary ligands into/from a robust yet flexible proto‐Zr‐MOF. This PVSI process features precise positioning of spacers with different length, size, number, and functionality, enabling accurate fixation of successive breathing stages and fine‐tuning of pore surface. It shows unprecedented synthetic tailorability to create complicated MOFs in a predictable way for property modification, for example, CO2 and R22 adsorption/separation, thermal/chemical stability, and extended breathing behavior. Abstract : Bringing PSM into dynamic MOFs : Post‐synthetic modification (PSM) is used to install/uninstall varied linkers into/from a flexible Zr‐MOF. This post‐synthetic variable‐spacer installation (PVSI) strategy is used to tune elastic deformation, breathing behavior, and stabilization of the framework in controllable and predictable way. Tuning the pore surface leads to a larger surface area and improved gas separation and adsorption capacity.